Incidence and predictors of under-five mortality in East Africa using multilevel Weibull regression modeling - Getayeneh Antehunegn Tesema; Achamyeleh Birhanu Teshale; Zemenu Tadesse Tessema (BMC, 2021)
Abstract Background In 2017, an estimated 5.3 million under-five children died annually in Sub-Saharan African countries, more than half of those deaths occurred in East Africa. Though East African countries share the huge burden of global under-five mortality, there is limited evidence on the incidence and predictors of under-five mortality. Therefore, this study investigated the incidence and predictors of under-five mortality in East Africa. Methods A community-based cross-sectional study was done based on the Demographic and Health Survey (DHS) data of 12 East African countries conducted from 2008 to 2019. A total weighted sample of 138,803 live births within 5 years preceding the survey were included for analysis. The Kaplan-Meier curve and Log-rank test were done to assess the children's survival experience across variable categories. The Global Schoenfeld residual test was employed for checking Proportional Hazard (PH) assumptions and it was violated (p-value< 0.05). Considering the hierarchical nature of DHS data, multilevel parametric survival models were fitted. Model comparison was made by AIC, deviance, and shape of the hazard function. Variables with a p-value of less than 0.2 in the bi-variable analysis were considered for the multivariable analysis. In the multilevel Weibull regression analysis, the Adjusted Hazard Ratio (AHR) with 95% Confidence Interval (CI) was reported to declare the significant predictors of under-five mortality. Results Under-five mortality rate in East Africa was 51.318 (95% CI: 51.311, 51.323) per 1000 live births. Babies born to mothers attained secondary education and above (AHR = 0.83, 95% CI: 0.75, 0.91), being 2nd - 4th birth order (AHR = 0.62, 95% CI: 0.56, 0.67), ≥ 5th birth order (AHR = 0.68, 95% CI: 0.61, 0.76), health facility delivery (AHR = 0.87, 95% CI: 0.82, 0.93), 1-3 ANC visit (AHR = 0.61, 95% CI: 0.54, 0.68), births interval of 24-48 months (AHR = 0.53, 95% CI: 0.50, 0.57), wanted pregnancy (AHR = 0.72, 95% CI: 0.68, 0.76), middle wealth status (AHR = 0.90, 95% CI: 0.83, 0.97), and richest wealth status (AHR = 0.81, 95% CI:0.73, 0.90) were significantly associated with lower hazards of under-five mortality. Whereas, advanced maternal age (≥35 years) (AHR = 1.13, 95% CI: 1.04, 1.24),, babies born to household who did not have media exposure (AHR = 1.13, 95% CI: 1.07, 1.20), twin births (AHR = 3.81, 95% CI: 3.52, 4.12), being male child (AHR = 1.27, 95%CI: 1.21, 1.33), small birth size at birth (AHR = 1.73, 95% CI: 1.63, 1.84), and large size at birth (AHR = 1.11, 95% CI: 1.04, 1.11) were significantly associated with higher hazards of under-five mortality. Conclusion Under-five mortality is a major public health concern in East African countries. Health facility delivery, ANC visit, higher wealth status, adequate birth spacing, wanted pregnancy, and maternal education were significantly correlated with a lower risk of under-5 mortality. Whereas, higher birth order, small or large size at birth, male birth, twin birth, advanced maternal age and mothers who didn't have media exposure were significantly correlated with a higher risk of under-five mortality. This study highlights that public health programs should enhance health facility delivery, ANC visit, media exposure, maternal education, and adequate birth spacing to decrease the incidence of under-five mortality in East Africa.